2015
DOI: 10.1016/j.elspec.2014.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Bulk and surface band structure of the new family of semiconductors BiTeX (X=I, Br, Cl)

Abstract: a b s t r a c tWe present an overview of the new family of semiconductors BiTeX (X = I, Br, Cl) from the perspective of angle resolved photoemission spectroscopy. The strong band bending occurring at the surface potentially endows them with a large flexibility, as they are capable of hosting both hole and electron conduction, and can be modified by inclusion or adsorption of foreign atoms. In addition, their trigonal crystal structure lacks a center of symmetry and allows for both bulk and surface spin-split b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
24
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 40 publications
5
24
1
Order By: Relevance
“…This is in good agreement with the reported difficulty of exfoliating layers in bismuth tellurohalides [26,54]. This behavior can be understood if we consider that layers in bismuth tellurohalides are asymmetric (Te-Bi-Br) while in the other two families they are symmetric (Se-Bi-Se-Bi-Se or Se-In-In-Se).…”
Section: -6supporting
confidence: 79%
See 2 more Smart Citations
“…This is in good agreement with the reported difficulty of exfoliating layers in bismuth tellurohalides [26,54]. This behavior can be understood if we consider that layers in bismuth tellurohalides are asymmetric (Te-Bi-Br) while in the other two families they are symmetric (Se-Bi-Se-Bi-Se or Se-In-In-Se).…”
Section: -6supporting
confidence: 79%
“…Our measurements of the full width at half maximum of this Raman mode in BiTeBr (see Fig. S4 in [46]) also shows the same behavior but it was interpreted as due to its particular morphology of the two-phonon density of states and the way the frequency of the first-order mode sweeps the two-phonon density of states as pressure increases [54].…”
Section: -6mentioning
confidence: 50%
See 1 more Smart Citation
“…The narrow-gap semiconductors BiTeX (X = Cl, Br, I) have attracted considerable interest because of large Rashba-type spin-orbit splittings in their bulk and surface electronic structures [1][2][3], which have been observed by angle-resolved photoelectron spectroscopy (ARPES) [4][5][6][7][8] and magnetotransport measurements [9,10]. The enhanced spin-splitting in these materials is driven by their non-centrosymmetric crystal structure in combination with strong atomic spin-orbit coupling and a negative crystal-field splitting of the topmost valence bands [11].…”
Section: Introductionmentioning
confidence: 99%
“…Fiedler et al [9] investigated the surface structural and electronic properties of the semiconductors BiTeX (X D Cl, Br, I) using the various techniques. Moreschiniet et al [16] investigated the surface states using the QUANTUM-ESPRESSO package. Dubeyet et al [17] observed that SbTeI showed metallic behavior from 4 K to 300 K and semiconducting behavior at higher temperature (>300 K).…”
mentioning
confidence: 99%